2018
DOI: 10.1111/acem.13562
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Risk of Future Suicidality in Emergency Department Patients

Abstract: Background.-Emergency Departments (ED) are the first line of evaluation for patients at risk and in crisis, with or without overt suicidality (ideation, attempts). Currently employed triage and assessments methods miss some of the individuals who subsequently become suicidal. The Convergent Functional Information for Suicidality (CFI-S) 22 item checklist of risk factors, that does not ask directly about suicidal ideation, has demonstrated good predictive ability for suicidality in previous studies in psychiatr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 22 publications
(20 reference statements)
0
16
0
Order By: Relevance
“…[26, 27] At least 40% of ED patients with medically unexplained or chronic pain have moderate to severe situational anxiety, and a larger fraction admit to severe chronic stress. [1, 3, 28] Challenges to initiating therapy dogs include the administrative hurdles required to obtain hospital credentials for therapy dogs and handlers to visit the ED, including “worst-case” concerns over possible patient phobias for dogs, allergies, zoonotic infections, and hygiene. Other challenges include the fact that dogs and handlers are not uniformly available, yet EDs are always open.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[26, 27] At least 40% of ED patients with medically unexplained or chronic pain have moderate to severe situational anxiety, and a larger fraction admit to severe chronic stress. [1, 3, 28] Challenges to initiating therapy dogs include the administrative hurdles required to obtain hospital credentials for therapy dogs and handlers to visit the ED, including “worst-case” concerns over possible patient phobias for dogs, allergies, zoonotic infections, and hygiene. Other challenges include the fact that dogs and handlers are not uniformly available, yet EDs are always open.…”
Section: Discussionmentioning
confidence: 99%
“…A convenience sample survey of 338 urban emergency department patients found that 81% of patients answered yes to the question “Have you experienced acute stress within last 3 months (a major financial, professional, or personal loss or loss/death of a loved one? ).”[1] Approximately 8% of patients with low risk chest pain spontaneously reported anxiety as the primary reason for their ED visit at 90-day follow-up. [2] When surveyed prospectively in the ED, 40% of low risk chest pain patients scored >7 on the anxiety subscale of the Hospital Anxiety and Depression Survey.…”
Section: Introductionmentioning
confidence: 99%
“…However, one of the other objectives could be protecting the emergency staff from any possible risks and damages. Moreover, the procedure of specifying possible risks consists of recognition of the situations which place the patients or the emergency staff in various dangerous positions [16]. On the other hand, because in the last five decades the number of reported risks in emergency departments was not too high, the number of conducted investigations on this issue was not enough for making standardized recommendations on it which maybe was due to the lack of insufficient knowledge about the issue of risk management.…”
Section: The Emergence Of Risk Management Issue In Edsmentioning
confidence: 99%
“…Even though most of the patients with chest pain who attended emergency departments are not in very life-threatening conditions, the process of immediate and precise diagnosis of their disorder could be very challenging. On the other hand, the improper diagnosis would be very risky and lead to harmful and incorrect therapies which may increase the rate of morbidity and mortality [16], [26]. https://www.id-press.eu/mjms/index Some other major conditions and complaints that are at higher risks and frequently could happen in emergency departments include Acute coronary syndrome (ACS), Pulmonary embolism, Aortic dissection (AD), Acute or/and chronic stomach pain, Abdominal aortic aneurysm, Appendicitis, Headache, Subarachnoid haemorrhage (SAH), Stroke, Pediatric fever, Meningitis, Airway problems, Polytrauma, Head injury, Spinal cord injury (SCI), Open wounds, Any bone fractures, Testicular torsion, Extrauterine pregnancy, and Septicemia [27], [28].…”
Section: Evaluation Of High-risk Conditionsmentioning
confidence: 99%
“…The Convergent Functional Information for Suicidality (CFI‐S) is a validated screening tool for suicidal ideation, but it has not been tested in an ED setting . The current trial aimed at assessing the accuracy of the CFI‐S in the ED, while comparing it to a screening tool already in use and physician gestalt …”
Section: Introductionmentioning
confidence: 99%